FORMULAS DERIVADAS



REGLAS DE DERIVACIÓN

(f + g)' = f'' + g'

ejemplo (3x^2+5x)' = (3x^2)'+(5x)
= 6x + 5

(f * g)' = f.g' + g.f '

ejemplo
(3x^2*5x^3 - 8x)' = 3x^2 * (15x^2-8) + x^3-8x)(6x)

45x^4-24x^2+30x^4-48x^2
= 75x^4 - 72x^2

(f/g)'= g*f'' - f *g' / g^2

3x^2/5x^3-8x = (5x^3-8x)(6x)-(3x^2)*(15x^2-8)/(5x^3-8x^2)

= (30x^4-48x^2)-(45x^4+24x^2)/(5x^3-8x)^2
=30x^4-48x^2-45x^4+24x^2/(5x^3-8x)^2
=-15x^4-24x^2/(5x^3-8x)^2






Share this

Related Posts

Previous
Next Post »

Buscar en Wikipedia

Resultados de la búsqueda